Program usposabljanj za zdravstveno varstvo rastlin in preprečevanje širjenja škodljivih organizmov – Better Training for Safer Food (BTSF) - Capuder, Luka (Gozdarski vestnik, 2026)
Better Training for Safer Food (BTSF) trainings, organized on the initiative of the European Commission, are crucial for strengthening expertise and ensuring the harmonized implementation of phytosanitary measures in the European Union, as they enable a better understanding of legislation, early detection of quarantine pests, and more effective responses in the event of pest outbreaks. In 2025, individual phytosanitary inspectors employed at the Slovenian Forestry Institute and the Slovenia Forest Service attended three trainings: “Plant Health Surveys”, focused on planning and conducting survey programs; “New Plant Health Regime”, which addressed EU legislation, pest categorization, and the control of host commodity movements; and “Contingency Planning for Priority Pests”, centred on preparing contingency action plans in response to outbreaks of priority quarantine pests. The trainings included theoretical content, field demonstrations, case analyses, and simulations of emergency events, providing practical insight into phytosanitary procedures and facilitating the exchange of best practices among EU Member States. The knowledge gained will be used to improve the design and implementation of national survey programs, strengthen interinstitutional cooperation, update emergency response procedures, and enhance communication with the public and stakeholders, thereby contributing to better preparedness for phytosanitary risks in Slovenia and to a more harmonized and reliable plant health system at the EU level.
Keywords: contingency plans; karantenski škodljivi organizmi; legislation; načrti izrednih ukrepov; plant health protection; plant health survey programmes; programi preiskav; quarantine pests; zakonodaja; zdravstveno varstvo rastlin